Goldenhar syndrome: An ephialte for the anesthesiologist – What we saw was just the tip of the iceberg - Nidhi Sultania,; Priyanka Bansal, (Asian Journal of Medical Sciences, 2024)
Goldenhar syndrome, also called oculoauriculovertebral dysplasia, is characterized by craniofacial, central nervous system, cardiac, renal, and vertebral anomalies. It occurs due to the faulty unilateral development of vertebral arches. Patients presenting for surgery are usually in the pediatric age group. General anesthesia is the preferred mode of anesthesia considering the type of surgery, age of the patient, and vertebral anomaly in this patient group. The first and foremost consideration while anesthetizing these patients is the anticipated difficult airway. Frequently encountered airway abnormalities in these patients are micrognathia, retrognathia, mandibular dysplasia, craniovertebral anomalies leading to limited neck flexion and cervical spine instability, decreased thyromental distance, fascial asymmetry, cleft lip and palate, high arched palate, dental abnormalities, and temporomandibular joint abnormalities. Difficult airways often come disguised as syndromes, and thorough pre-operative evaluation along with preparation for the worst scenarios is a must. We have a myriad of alternative airway management equipment at our disposal. Adequate knowledge is a must for their best use.